Dialektika Poligami dengan Feminisme : Analisis Maqasid Syariah Terhadap Poligami Menurut Ulama Klasik dan Feminisme - Mohammad Lukman Chakim; Muhammad Habib Adi Putra (Al-Syakhsiyyah: Journal of Law & Family Studies, 2022)
The practice of polygamy was circulated long before the arrival of Islam. Polygamy is believed to have existed long before Islam came and was already practiced by humans around the world, they did it, and made it part of the dynamics of normal life. That being said, no civilization of that era was alien to polygamy. Studies of polygamy today are growing and crowded, where the classic opinion that is mostly pro-polygamy is widely protested by feminists. According to feminism, that polygamy should be tightened or precisely abolished. The pros and cons of polygamy with feminism are so extraordinary, in Indonesia this discourse can be seen in the CLD-KHI. For that the author makes the focus of the question a). how polygamy according to classical scholars and feminism and b). how is the sharia maqasid analysis of the dialectic of polygamy with feminism. This research was conducted using a literature research method  with primary sources in the form of books related to the views of classical scholars and feminism and supported by secondary sources that will be analyzed with a maqasid-based dialectic approach. Departing from the above, the author is interested in conducting research with the aim of providing a middle ground for the two camps, by providing dialectics, through sharia maqasid it is hoped that it will be able to provide concepts or rules about polygamy that represent the two camps, the view of classical ideas and the Marriage Law Number 1 of 1974 and the discourse of polygamy in the view of feminism.